Modified slotted shear test for a thin sheet of solid polymer under large deformations. (August 2015) - Nunes, L.C.S.
Abstract: A modified slotted shear test based on ASTM B831 is proposed and used for determining the mechanical behavior of a solid polymer at large deformations. The shear stress-strain response of a thin sheet of polytetrafluoroethylene was experimentally investigated and a V-notched rail shear test was carried out to validate the experimental results obtained with the proposed approach. Displacement and strain fields of the test specimens were estimated by the Digital Image Correlation method. The results indicate agreement between both tests for small deformations, while for large deformations significant discrepancies in shear stress-strain responses are observed. These discrepancies can be attributed to unwanted distortions of the gage section observed in the V-notched specimens. The modified slotted shear test provided a uniform shear strain distribution across the gauge section of specimens. In addition, the principal advantages of the proposed approach over V-notched rail shear test are a wide range of shear strains and absence of unwanted distortions.